Determinants of the Formation and Activity of Factor V-phospholipid Complexes II. Molecular Properties of the Complexes - Kandall, Carol L; Shohet, Stephen B; Akinbami, T. K; Colman, Robert W (Thrombosis and Haemostasis, 1975)
The stability, buoyancy, and intrinsic activity of factor V-phospholipid complexes were investigated.The decay of factor V activity in the absence of phospholipid followed first order kinetics; however, in the presence of several phospholipids a biphasic decay curve was observed. The addition of phosphatidylethanolamine to factor V produced only a small loss of activity in the first 2 minutes but decreased the subsequent rate of inactivation fourfold. A PE-factor V complex with a low bouyant density was separated from uncomplexed factor V by sucrose density ultracentrifugation. The association constant for this complex was 5 × 106 M-1 with approximately 2 moles of factor V bound per mole of lipid micelle. The isolated complex was capable of increasing prothrombin conversion 10-fold without additional phospholipid. A still lighter complex increased the rate of prothrombin conversion 18-fold.Phosphatidyl serine produced a concentration-dependent loss of up to 95% of the factor V activity in the first 2 minutes. After ultracentrifugation on a sucrose density gradient, a PS-factor V complex of increased density was detected. This complex failed to accelerate prothrombin conversion in the intrinsic two-stage assay.Except at very high concentrations, phosphatidylcholine did not alter the kinetics of inactivation of factor V. A factor V-phosphatidylcholine complex could not be detected after ultracentrifugation.When added to factor V, cardiolipin (200 μg/ml), produced a rapid 50% decline in activity with a subsequent three-fold increase in the rate of inactivation. No activity was recovered after ultracentrifugation of factor V in the presence of cardiolipin.Saturated phosphatidylethanolamine produced a concentration dependent initial loss of activity, but only a minimal increase in the subsequent rate of inactivation. At 200 μg/ml almost no light complex was detected after ultracentrifugation, but at 800 μg/ml a light complex was observed. This behavior corresponds to the ability of saturated phosphatidylethanolamine to accelerate prothrombin conversion only at very high concentrations.Thus, phospholipids combine with factor V to form complexes which differ in their ability to accelerate prothrombin conversion. The most active species are stable lipoprotein complexes of lower buoyant density than factor V.